KONSEP KEBAHAGIAAN MENURUT IBN MISKAWAIH - Iqbal, Imam (P3M STAIN Sorong, 2016)
Ibn Miskawayh in the world of eastern philosophy becomes one of the leaders in the field of ethical philosophy. Their thinking is so sharp and revealing many good values in human life. Happiness, according to Ibn Miskawayh is the culmination and perfection of goodness. Something can be called perfect if only after something is gained, then people will not need anything else. Happiness in this perspective cannot be achieved by everyone and only enjoyed by those special and perfect. Studies on happiness in the thinking of Ibn Miskawayh begin with the perspective of a human. He said humans have a spiritual virtue, by which he can emulate the good spirits, often called angel. He also has a physical virtue, by which he can match the animals because human beings are composed of these two virtues. Armed with the physical, with which he can match the animals, humans lived in this nether world in a relatively short period of time, to prosper well organize and regulate this nature.